IMPORTANCE OF CORPORATE SOCIAL RESPONSIBILITY IN BRAND VALUE OF FRUITS AND VEGETABLES (Proceedings of the International Conference on Agriculture, 2019)
Brand equity on products such fruits and vegetables is a topic that has not yet been extensively studied as they are often perceived by consumers as a low value added and thus very sensitive to price competition.  A revision of this value proposition is very relevant nowadays as there are more fruits and vegetables new brands that are coming and entering the market. The aim of this study is to validate the brand equity scale for fruits and vegetables and to configure whether any of the brand value dimensions are the factors for a consumer to pay for a premium price. The background of this study is backed by quantitative survey of fresh produce consumers in Spain. The survey shows that Corporate Social Responsibility (CSR) is one of the significant determinants of a consumer to pay for a premium price for a specific fruit. We can conclude that consumer’s gives more emphasis to a brand that has strong Corporate Social Responsibility (CSR) additionally this may have strong implications in brand management and corporate benefits in fruit and vegetables companies.
Keywords: brand value; Fruit; CSR; premium price